Romania's external debt: Trend and characteristics after the accession to the European Union - Camelia Milea (Financial Studies, 2018)
The paper aims to argue the importance of the external debt and of its structure for the management of macroeconomic policies. The survey focused on the period 2006-2017, in order to reveal the effects of Romania's joining the European Union on the trend of the external debt of and of its components. During the analysed period, the medium and long-term external debt held the majority within Romania's total external debt. The evolution of the external debt and of its components had a turning point in 2013 when, for the first time in the surveyed period, they started to diminish. The structure by creditors of the medium and long-term external direct public debt shows that the multilateral credits formed the majority of the debt in 2006-2012, while the share of bonds issues increased in 2013-2017. The almost continuous increase of NBR's (National Bank of Romania) reserve assets shows Romania's financial and banking solidity and credibility.
Keywords: F21; F32; F34; H63; 330; external debt structure; external direct public debt; debt problems; creditors